O processo de desenvolvimento e aprendizado da libras por alunos ouvintes em narrações de histórias - Ribeiro, Jéssica do Amaral (Universidade Federal de São Carlos, 2023)
The present work aims to analyze how listening students of the Libras/Portuguese Translation and Interpretation Course (TILSP) learn Libras as a second language in the classroom context, based on systematized teaching processes. More specifically, the emphasis is on learning aspects related to the use of the body and the signaling space to organize the scenarios and actions in a storytelling in Libras. The use of these resources, employed in a discursive strategy called 'demonstration' (Clark, 1996; SILVA, 2014), are elements that relate to visually perceptible aspects of the stories narrated in these languages. This work is based on other research that has already been discussing the elements that characterize the teaching of Libras in universities and on learning processes (MARTINS, NASCIMENTO, 2015). For our research, we analyzed two of my own productions in Libras, made in the course entitled “Deafness and visuality”, taught by a deaf teacher. The main activity analyzed is a video recorded on the first day of class, retold in the last class of the semester. With this, we analyzed the productions with the objective of identifying factors that show us advances in the teaching-learning process. With these analyses, we describe part of the Libras learning process in interaction and pedagogical mediation within the university.
The process of development and learning of Libras by hearing students in storytelling settings
Keywords: Libras; Aprendizagem; Narrativas; Brazilian sign language; Learning; Narratives; LINGUISTICA, LETRAS E ARTES